Mortality of native and invasive ladybirds co-infected by ectoparasitic and entomopathogenic fungi - Haelewaters, Danny; Hiller, Thomas; Kemp, Emily A; van Wielink, Paul S; Shapiro-Ilan, David I; Aime, M Catherine; Nedvěd, Oldřich; Pfister, Donald H; Cottrell, Ted E (PeerJ, 2020)
Harmonia axyridis is an invasive alien ladybird in North America and Europe. Studies show that multiple natural enemies are using Ha. axyridis as a new host. However, thus far, no research has been undertaken to study the effects of simultaneous infection by multiple natural enemies on Ha. axyridis. We hypothesized that high thallus densities of the ectoparasitic fungus Hesperomyces virescens on a ladybird weaken the host's defenses, thereby making it more susceptible to infection by other natural enemies. We examined mortality of the North American-native Olla v-nigrum and Ha. axyridis co-infected with He. virescens and an entomopathogenic fungus-either Beauveria bassiana or Metarhizium brunneum. Laboratory assays revealed that He. virescens-infected O. v-nigrum individuals are more susceptible to entomopathogenic fungi, but Ha. axyridis does not suffer the same effects. This is in line with the enemy release hypothesis, which predicts that invasive alien species in new geographic areas experience reduced regulatory effects from natural enemies compared to native species. Considering our results, we can ask how He. virescens affects survival when confronted by other pathogens that previously had little impact on Ha. axyridis.
Keywords: Parasites; Invasive alien species; Harmonia axyridis; Coccinellidae; Fungal entomopathogens; Enemy release hypothesis; Native species; Hesperomyces virescens